Efficacy and safety of nerinetide in acute ischaemic stroke in patients undergoing endovascular thrombectomy without previous thrombolysis (ESCAPE-NEXT): a multicentre, double-blind, randomised controlled trial - Hill, Michael D.; Pham, Mirko; Bode, Felix J.; Mundiyanapurath, Sibu; Witt, Karsten (The lancet, 2025)
Background - In the ESCAPE-NA1 trial, treatment with nerinetide, an eicosapeptide that interferes with post-synaptic density protein 95, was associated with improved functional outcome among patients with acute ischaemic stroke due to large vessel occlusion undergoing endovascular thrombectomy without co-treatment with an intravenous thrombolytic agent. There was no benefit when intravenous thrombolytic agent co-treatment was used. We sought to confirm the clinical benefit of nerinetide in the absence of previous intravenous thrombolytic drug treatment. - Methods - In this multicentre, randomised, double-blind, placebo-controlled study, done in 77 centres in Canada (16), the USA (16), Germany (21), Italy (four), the Netherlands (three), Norway (four), Switzerland (three), Australia (eight), and Singapore (two), we enrolled patients with acute ischaemic stroke due to anterior circulation large vessel occlusion within 12 h from onset. Eligible patients were aged 18 years or older with a disabling ischaemic stroke at the time of randomisation (baseline National Institutes of Health Stroke Scale [NIHSS] score >5), who had been functioning independently in the community (Barthel Index score >90) before the stroke, had Alberta Stroke Program Early CT Score (ASPECTS) greater than 4, and who were not treated with a plasminogen activator. Patients were randomly allocated (1:1) to receive intravenous infusion of nerinetide in a single dose of 2·6 mg/kg, up to a maximum dose of 270 mg, based upon estimated or actual weight (if known) or saline placebo using a real-time, dynamic, internet-based, stratified randomised minimisation procedure. All patients underwent endovascular thrombectomy. The primary outcome was a favourable functional outcome 90 days from randomisation, defined as a modified Rankin Scale (mRS) score of 0-2. The analysis was by intention to treat and adjusted for time from stroke onset to randomisation (≤4·5 h [yes or no]), age, sex, baseline NIHSS score, occlusion location, time from qualifying imaging to randomisation, baseline ASPECTS, and region. Secondary outcomes were measures of mortality, worsening of stroke, improved functional independence, and measures of neurological disability. This trial is registered with ClinicalTrials.gov, NCT04462536. - Findings - From Dec 6, 2020, to Jan 31, 2023, 850 patients were assigned to receive nerinetide (n=454) or placebo (n=396). 206 (45%) participants in the nerinetide group and 181 (46%) participants in the placebo group achieved an mRS score of 0-2 at 90 days (odds ratio 0·97, 95% CI 0·72-1·30; p=0·82). Serious adverse events occurred equally between groups. - Interpretation - While nerinetide did not improve outcomes in patients with acute ischaemic stroke, it was not associated with excess adverse events. Further study is needed to identify the ideal timing of treatment and the sub-population of stroke patients who might benefit from treatment combined with current reperfusion therapies. - Funding - Canadian Institutes for Health Research and NoNO.
Online verfügbar: 13. Februar 2025
Gesehen am 10.09.2025